Relationship among periodontal disease, insulin resistance, salivary cortisol, and stress levels during pregnancy - Seraphim, Ana Paula Castilho Garcia [UNESP]; Chiba, Fernando Yamamoto [UNESP]; Pereira, Renato Felipe [UNESP]; Mattera, Maria Sara de Lima Coutinho [UNESP]; Moimaz, Suzely Adas Saliba [UNESP]; Sumida, Doris Hissako [UNESP] (FapUNIFESP (SciELO), 2016)
Pregnancy is a period involving important metabolic changes that enable the maintenance of the mother’s health and development of the fetus. This study aimed to assess the relationship among periodontal disease, insulin resistance, salivary cortisol concentration and level of perceived stress in pregnant women. This was a cross-sectional study. The sample comprised 96 pregnant women between the fifth and seventh month of pregnancy registered at the Basic Health Units of the Unified Health System (SUS). The periodontal condition was assessed after obtainment free and informed consent from the participants. Participants were divided into three groups: control subjects with a healthy periodontal condition (CN; n=46), patients with gingivitis (GI; n=26), and patients with periodontitis (PI; n=24). Saliva and blood samples were collected for evaluation of salivary cortisol concentration, glycemia, insulinemia and Homeostasis Model Assessment-Insulin Resistance index. A validated survey for the assessment of perceived stress levels was also performed. PI group showed significantly higher (p<0.05) blood glucose levels (CN: 4.43±0.05; GI: 4.46±0.04; PI: 4.68±0.08), insulinemy (CN: 6.93±0.45; GI: 8.87±0.79; PI: 12.77±1.30), insulin resistance (CN: 1.40±0.10; GI: 1.81±0.18; PI: 2.66±0.29) compared with the CN and GI groups. The levels of perceived stress were higher (p<0.05) in PI and GI groups when compared to CN group (CN: 20.5±1.26; GI: 25.8±1.95; PI: 26.6±1.36). There was no significant difference in the concentration of salivary cortisol between the groups (CN: 11.13±0.58; GI: 11.96±0.74; PI: 11.47±0.74). It was concluded that there is a relationship between higher levels of perceived stress, insulin resistance and the occurrence of periodontal disease during pregnancy. This study emphasizes the importance of preventing periodontitis in order to avoid insulin resistance and stress during pregnancy since these can cause systemic complications for the mother and the fetus.
Keywords: Gestational diabetes; Hydrocortisone; Periodontal diseases; Physiological stress; Pregnancy